The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1155/2018/3760124
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of NP‐POL Nonapeptide for Possible Therapeutic Use in Parkinson’s Disease

Abstract: Colostrum and milk are the initial mammalian nourishment and rich reservoir of essential nutrients for newborn development. Bioactive peptides isolated from natural sources, such as colostrum, serve as endogenous regulators and can be used as alternative therapeutic agents in the treatment of neurodegenerative diseases. One example is the previously unknown NP-POL nonapeptide isolated from Colostrinin. In the present study, we investigated a method of NP-POL nonapeptide isolation using Bio-Gel P2 molecular sie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…Previous studies have demonstrated that 6-OHDA induce neurotoxicity in PC12 cells to construct a cellular model of PD. [22][23][24][25] Firstly, the cytotoxic effect of 6-OHDA on PC12 cells were measured via a CCK8 assay. PC12 cells were treated with different doses of 6-OHDA (50, 100, 150, and 200 mM) for 24 h; at concentrations of over 50 mM the viability of PC12 cells was significantly affected, and a concentration of 100 mM or higher did not decrease the cell viability (Fig.…”
Section: Sal Alleviated 6-ohda-induced Injury In Pc12 Cellsmentioning
confidence: 99%
“…Previous studies have demonstrated that 6-OHDA induce neurotoxicity in PC12 cells to construct a cellular model of PD. [22][23][24][25] Firstly, the cytotoxic effect of 6-OHDA on PC12 cells were measured via a CCK8 assay. PC12 cells were treated with different doses of 6-OHDA (50, 100, 150, and 200 mM) for 24 h; at concentrations of over 50 mM the viability of PC12 cells was significantly affected, and a concentration of 100 mM or higher did not decrease the cell viability (Fig.…”
Section: Sal Alleviated 6-ohda-induced Injury In Pc12 Cellsmentioning
confidence: 99%
“…43 Another study demonstrated that the active ingredient in colostrinin reduced rather than induced the neurotoxicity of adrenal pheochromocytoma cells that was induced by 6-hydroxydopamine, via transient activation of the ERK pathway. 44 Lactoferrin protects the neuronal cell by stabilizing the hypoxiainducible factor-1α via its up-regulatory effects on the prolyl hydroxylase enzyme and thereby prevents the formation of the abnormal isoform prion protein. 45 Other researchers demonstrated that insulin growth factor-1, which is available in the BC, plays an important role in the suppression of neurodegeneration via its effect on the generation of reactive oxygen species and improves mitochondrial function by blocking the effect of the cellular prion protein upon the mitochondria.…”
Section: Counteract Inflammation That Is Implicated In the Deteriorat...mentioning
confidence: 99%